Prediction of Residual Stresses in 316 Stainless Steel Pipes Welded Joint - Mutair, Zahraa A.; Mohammad, and Haider M. (Basrah Journal for Engineering Sciences, 2023)
Due to the extremely complicated thermal cycle for the welding process, the fusion zone and heat-affected zone (HAZ) produce irreversible elastic-plastic deformation and residual stresses. The differential heating of the pipes caused by the weld heat source causes residual stress as a result of the welding process. However, the strength and lifetime of the component are also decreased as a result of residual stresses in and around the weld zone. The objective of this research is to analyze the residual stresses created during the welding process and select the best welding parameters that give the lowest residual stresses in 316SS pipes with 50 mm diameter and 4 mm thickness that were manually welded by used (316) welding wire and using shielded metal arc welding (SMAW) in a single-pass butt joint with the various values for each of current (58 , 68 , 78 , 88) amperes and voltage (22 , 23 , 24 , 25 , 26) volts. The shielded metal arc welding process involves heating, melting, and solidifying the parent metals and filler material in a localized fusion zone by a transient heat source to create a junction between the parent metals. The welding process free from preheating and heat treatment will be obtained. ANSYS Finite Element methods are used to calculate the welding residual stress distribution. The mechanical and thermal models were used to carry out the theoretical analysis. In general, the numerical study found that the residual stress distribution at the weld zone’s center is continuous, rising, and has a value of about (1738 MPa). Additionally, the residual stress at the boundary between the heat-affected zone and the weld zone climbs to a maximum value of around (3799 . 6 MPa). On the other hand, the magnitude of the residual stress in the heat-affected zone of the weld reduces significantly and achieves a minimum value at a position of (20 mm) with a value near zero.